Effect of different intracanal medicaments on eradication of Enterococcus faecalis biofilm – Ex vivo study - Hesham Moheb; Samira Zakeer; Hayam Y. Hassan (Saudi Endodontic Journal)
Introduction: To compare the effect of different intracanal medicaments on Enterococcus faecalis (E. faecalis) biofilm inside root canals using the viable count method (colony forming unit [CFU]/mL) and scanning electron microscope (SEM). Materials and Methods: A total of 180 mandibular premolars were selected. Access cavities, cleaning and shaping were done. After sterilization, all the teeth were inoculated by E. faecalis for 5 weeks to establish a mature biofilm. The inoculated roots were equally distributed into six experimental groups corresponding to the powder used: Calcium hydroxide Ca(OH)2; metronidazole (MDZ) and chitosan. Each powder was mixed with two different vehicles, 2%chlorhexidine (CHX) solution and sterile water, as an intracanal dressing for 2 weeks. Twenty infected root canals were representing the positive control group, and other 20 noninfected root canals represented the negative control group. To determine the bacterial load (CFU/mL), samples were collected by sterile paper points pre and postdressing. Using an SEM, the root canals from each group were topographically scanned. Kruskal–Wallis and Mann–Whitney U tests (post hoc test) were used to estimate and statistically analyze the bacterial reduction data (P < 0.05). Results: Mature biofilm formation was confirmed using SEM after incubation period. MDZ + CHX and Ca(OH)2 + CHX were significantly better than other intracanal medicaments (P < 0.05). The difference in antimicrobial effectiveness between other intracanal medications was not statistically significant. Conclusion: The combination of MDZ + CHX and Ca(OH)2 + CHX recorded a significant effect against E. faecalis biofilm among the intracanal medicament used.